High-quality and phenolic monomer-rich bio-oil production from lignin in supercritical ethanol over synergistic Ru and Mg-Zr-oxide catalysts - Limarta, Susan Olivia; Kim, Hanbyeol; Ha, Jeong-Myeong; Park, Young-Kwon; Jae, Jungho (ELSEVIER SCIENCE SA, 2020)
The efficient depolymerization of technical lignin to produce high-quality and phenolic monomer-rich bio-oil is challenging owing to the inherent recalcitrant structure of lignin. In addition, the phenolic fragments formed during lignin depolymerization are highly reactive and easily undergo rapid repolymerization to yield undesired heavy oils or char. In the present work, we report a new hybrid catalyst of Ru/C combined with MgO/ZrO2 that is highly effective at depolymerizing lignin to high-quality bio-oil by a cooperative catalysis of Ru-catalyzed reductive depolymerization and MgO/ZrO2-catalyzed stabilization of the reactive phenolic monomers through in-situ capping of the phenol repolymerization initiator, i.e., formaldehyde, by reaction with ethanol. A screening study of various catalyst combinations, including transition metal catalysts such as Pd, Ni, and Ru supported on carbon or Al2O3 as well as basic oxide catalysts such as MgO, MgO/ZrO2, ZrO2, and Mg-Al mixed oxides, revealed that Ru/C-MgO/ZrO2 was the only combination that had a significant positive synergistic catalytic effect on lignin depolymerization, thereby highlighting its unique and exceptional activity. To elucidate the synergistic roles of Ru and MgO/ZrO2 in lignin depolymerization, their individual and integrated catalysis as well as the effect of the Mg/Zr ratio were systematically investigated through a comprehensive analysis of the bio-oil products using several techniques, including 2D heteronuclear single quantum coherence nuclear magnetic resonance spectroscopy (HSQC-NMR). A high bio-oil yield of 76.2 wt% with a low molecular weight of 401 g/mol, large HHV of 34.47 MJ/kg, and high phenolic monomer yield of 31.44 wt% was successfully obtained over the integrated catalyst of Ru/C and MgO/ZrO2 (Mg/Zr = 3) at 350 degrees C and 30 bar-H-2 after 4 h.
Keywords: ACID-HYDROLYSIS LIGNIN; EFFICIENT DEPOLYMERIZATION; HIGH-YIELD; CONVERSION; HYDROGENOLYSIS; STABILIZATION; CONDENSATION; HYDROCARBONS; ALCOHOLS; METAL